DEVELOPING ENGLISH MATERIALS FOR FINE ARTS STUDY PROGRAM STUDENTS AT THE FACULTY OF CULTURAL STUDIES OF UNIVERSITAS BRAWIJAYA - Ika - Puspitasari (EDUCAFL : Journal of Education of English as Foreign Language, 2018)
this study was aimed at developing an English textbook for the students of Fine Arts Study Program in Faculty of Cultural Studies of Universitas Brawijaya Malang. The study was based on the design of Research and Development by Borg and Gall (1983). Thus, this study involved several stages namely the needs analysis, development of product, expert validation, materials try-out, and the finished product as the final stage out of the series of stages suggested. Questionnaires were employed as one of the instruments to obtain data during the needs analysis. Semi-structured interview was also conducted to lecturers teaching English in those particular students. an expert was then requested for his involvement in validating the textbook and giving some suggestions for the improvement of the product. Try-out stage was carried out in the real class situation for the purpose of investigating the feasibility of the developed textbook. The final product of this study was in the form of a textbook consisting of six units in which each covered materials on three language skills (reading, speaking, and writing) plus those of vocabulary and grammar. This textbook was also completed with a guidebook for teacher containing the guideline fo each activity and the answer keys for the exercises.